1998
DOI: 10.1080/07315724.1998.10718768
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors Adversely Influencing the Glucose/Insulin System

Abstract: For the majority of people, particularly if they do not smoke, the food they eat is the largest controllable factor determining their long-term health. The disproportionate consumption of foods high in fat, especially high in saturated fat, and high in simple sugars at the expense of foods high in complex carbohydrate and unsaturated fat has the potential of inducing abnormal metabolic processes in a normal healthy individual and to promote chronic degenerative diseases. Some of the effects of individual macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…It was found that copper deficiency was associated with hepatic iron retention [8]. Iron is a strong oxidant which has the ability to generate reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that copper deficiency was associated with hepatic iron retention [8]. Iron is a strong oxidant which has the ability to generate reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and experimental studies showed that iron overload was associated with abnormalities of glucose homeostasis [8], whereas copper deficiency was associated with hepatic iron retention [8]. Magnesium has been postulated to play a role in glucose homeostasis and insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…In both muscle and adipose tissue, a high-fat diet resulted in decreased insulin receptor numbers, but no change in receptor affinity. The same diet has been shown to decrease insulinstimulated glucose transport and intracellular glucose metabolism (45). The type of fat and degree of saturation were also shown to play an important role for glucose metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…Some aboriginal communities of the Interior of the Pacific North-West are known to collect Balsamroot (Balsamorhiza sagittata) and slowly pit-cook it for many hours, which converts most of the inulin into its fructose components resulting in a sweet tasting foodstuff (Peacock 1998). Humans however have a limited ability to metabolize fructose and if over-consumed it can potentially have detrimental effects on human health (Fields 1998;Elliott et al 2002;Basciano et al 2005). As a consequence, no Compositae crop has been domesticated as a source of starchy carbohydrates, unlike other large angiosperm families, such as Poaceae or Solanaceae.…”
Section: Nutritional Considerationsmentioning
confidence: 96%